2013
DOI: 10.1063/1.4811176
|View full text |Cite
|
Sign up to set email alerts
|

Multiple states of finger propagation in partially occluded tubes

Abstract: Articles you may be interested inThe influence of the interfacial heat release on nonlinear convective oscillations in two-layer systems Phys. Fluids 25, 072106 (2013); 10.1063/1.4813607The effect of interface movement and viscosity variation on the stability of a diffusive interface between aqueous and gaseous CO2 Phys. Fluids 25, 074103 (2013);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…B. Thompson, A. L. Hazel and A. Juel of the channel height (de Lózar et al 2009;Pailha et al 2012;Hazel et al 2013). Thompson et al (2014) found that all finger propagation modes in partially occluded Hele-Shaw channels were qualitatively reproduced in an adapted version of the depthaveraged model used by McLean & Saffman (1981) to show that finite surface tension selects the half-width finger in unoccluded Hele-Shaw channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B. Thompson, A. L. Hazel and A. Juel of the channel height (de Lózar et al 2009;Pailha et al 2012;Hazel et al 2013). Thompson et al (2014) found that all finger propagation modes in partially occluded Hele-Shaw channels were qualitatively reproduced in an adapted version of the depthaveraged model used by McLean & Saffman (1981) to show that finite surface tension selects the half-width finger in unoccluded Hele-Shaw channels.…”
Section: Discussionmentioning
confidence: 99%
“…The bifurcation moves towards lower capillary numbers and eventually becomes subcritical as the occlusion height increases further. For yet higher occlusions, the asymmetric solution smoothly evolves into a localised asymmetric solution upon decrease of Ca, which can persist even at Ca = 0, the capillary static limit (Hazel et al 2013).…”
Section: Experimental Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…We solve for the perturbation function f (ζ ) numerically by writing it as a truncated Taylor series 42) and computing the N real coefficients {a j } N−1 j=0 , and the two real parameters a and U. We chose N = 200 for all our calculations after checking that this value of N gives the same solution for N = 400 (up to at least eight decimal places).…”
Section: (D) Numerical Schemementioning
confidence: 99%